Kindergarten Expectations and Outcomes: Understanding the Influence of Educator and Child Expectations on Children's Self-Regulation, Early Reading, and Vocabulary Outcomes. Issue 3 (3rd July 2019) - Timmons, Kristy
ABSTRACT: This research examines the influence of educator and child expectations on children's self-regulation, early reading, and vocabulary outcomes over two time points. Thirty educators (15 early childhood educators [ECEs] and 15 teachers) and 149 kindergarten children participated in the research. The educators participated in an expectation ranking questionnaire. Data collection with the children included an interview task and standardized and nonstandardized assessments. Results indicate that ECE and teacher expectations were congruent at Time 1 but dissonant at Time 2, with ECEs having significantly higher expectations for children's self-regulation, early reading, and vocabulary outcomes at Time 2. Path analyses were run to simultaneously test for direct and indirect (mediating) effects. Findings revealed that ECE and child expectations had significant positive direct effects on outcomes. The only significant direct effect from teacher expectations to child outcomes was for vocabulary, and this was a negative direct effect. This research has important and direct application to practice through professional development with pre- and in-service educators, specifically in considering the practices of high expectation educators.